Exploring The Emergence Of Pockets Of Productive State-Owned Enterprises In Developing Countries: A Comparative Study Of Two State-Owned Media Enterprises In Ghana - Koto, I.M. (University of Ghana, 2019)
Many scholars have found that, in the midst of ineffective and unproductive states in developing countries, there exists exceptionally well-performing public organizations that deliver their mandates effectively and productively. There is renewed research to understand why and how these pockets of effective and productive public organizations managed to emerge and persist in a context where failure of public organizations is the norm. The study explored the factors that have accounted for the emergence of Graphic Communications Group Limited (GCGL) as a pocket of productive state-owned enterprise in comparison to another state-owned media enterprise called New Times Corporation (NTC). NTC has struggled to make profit although it was converted into a limited liability company on the same date as GCGL in 1998. The research used opinion survey data collected from employees of NTC and GCGL, interviews with officials both organizations, and interviews with newspaper vendors as the primary data for answering the question of why and how GCGL emerged as a pocket of profitable enterprise. The study found that GCGL and NTC have had the same focused legal powers since the 1970s and they operate in the same free market economy. Consequently, these two public policy factors could not have accounted for the emergence of GCGL as a pocket of productivity at the expense of NTC. The factors that accounted for the emergence of GCGL as a pocket of productivity were performance-oriented management system and organizational proactivity pursued by the leaders of GCGL. The study recommend that reforms to improve the productivity of state-owned enterprises should move beyond enactment of formal-legal policies to focus on building performance-oriented management culture as well as promote organizational proactivity in the market.
MPhil. Public Administration
Keywords: Productive State-Owned Enterprises; Ghana; Developing Countries